Resentiment in the Narrative Structure of T. Shevchenko's "The Servant" ("Naimychka") (Shevchenko Studies, 2025)
The article deals with T. Shevchenko's story "The Servant" as an experience of reading the history of Ukraine in a psychological way, in the context of the dynamics of mentality, local culture of the ethnos, people, folklore and ethnography. Through resentment as a suppressed revenge and resentment and melancholy as its experience in time, the emotional background, the anthropological codes of the enslaved Ukrainian nation are studied. Emotions serve as a tool for understanding and creative objectification of colonial trauma, speech codes of an inverted, inverted, oppressed and torn world. The narrator turns into a kind of antiquarian, collector, biographer and memoirist, who collects memories at the level of impressions and feelings, cinematically connects disparate fragments of space into a holistic picture of the Ukrainian world, correlating the fate of the veiled woman with the historical tragedy of Ukraine.
Keywords: anthropology; narration; postcolonial; stereotype; stigma; emotion